Community Development Agency in Developing Village in The Lamongan District - Abid Muhtarom; Rizal Nur Irawan (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2017)
Coordination of development planning. In this case, in any development plans villages need for synergy or cooperation between the Institute for Community Empowerment with the head of the village, it is hoped development plan produced can suit the needs and capabilities of the village, which in turn leads to increasing the level of welfare of rural communities themselves.Type of research undertaken by researchers are included descriptive research with qualitative analysis method. The data collection techniques to do is study of literature, field studies. Analysis of the data used in this study are included qualitative analysis; Data collection, data reduction, data presentation and Withdrawal conclusion or verification.Privileges Institute for Community EmpowermentÂ  In Development In Rural System In the Village Administration is (1) Plan development by consensus, (2) Mobilize and increase community participation in the implementation of development, (3) Cultivate dynamic condition of society and increase resilience in the district that studied to perform the function and role in the development of the Institute for Community Empowerment must comply with the rules villages and villages that have been made. However, there are some good functions to be executed to enhance the development of the Institute for Community Empowerment, namely (1) As a means of community participation in planning and implementing development; (2) Cultivating understanding and appreciation and awareness of the Pancasila; (3) Digging, harness, potential and mobilize self-help mutual aid societies to develop; (4) As a means of communication between the Government and the community and between citizens themselves; (5) Improving the knowledge and skills of the community; (6) To foster and mobilize the potential of the youth in development; (7) Fostering cooperation between institutions in society for development; (8) Implementation of other tasks in order to help the village government to build resilience established.Keywords: Role of the Institute of Community and Rural Development.Â Â